Generations and protest in Eastern Germany: Between revolution and apathy - Philippe Joly (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
How is the protest behavior of citizens in new democracies influenced by their experience of the past? Certain theories of political socialization hold that cohorts reaching political maturity under dictatorship are subject to apathy. Yet, it remains unclear whether mobilization during the transition can counterbalance this effect. This article examines the protest behavior of citizens socialized in Eastern Germany, a region marked by two legacies: a legacy of autocracy and, following the 1989-90 revolution, a legacy of transitional mobilization. Using age-periodcohort models with data from the European Social Survey, the analysis assesses the evolution of gaps in protest across generations and time between East and West Germans. The results demonstrate that participation in demonstrations, petitions, and boycotts is lower for East Germans socialized under communism in comparison with West Germans from the same cohorts. This participation deficit remains stable over time and even increases for certain protest activities. – – Inwiefern ist das Protestverhalten von Bürgerinnen und Bürgern durch ihre Vergangenheit beeinflusst? Theorien politischer Sozialisation behaupten, dass Kohorten, die in autokratischen Regimen aufgewachsen sind, in geringerem Umfang politisch teilhaben, als Kohorten, die in demokratischen Systemen sozialisiert wurden. Jedoch ist unklar, welchen Einfluss Zeiten hoher politischer Mobilisierung während des Übergangs von autokratischen zu demokratischen Systemen auf das zukünftige Protestverhalten derjenigen haben, die den Umbruch miterleben. Fraglich ist, ob dies dem autokratischen Erbe der politischen Teilnahmelosigkeit entgegenwirken kann. Der vorliegende Beitrag untersucht das Protestverhalten von Bürgerinnen und Bürgern, die in Ostdeutschland aufgewachsen und sozialisiert wurden. Die Region der ehemaligen DDR zeichnet sich durch zwei politische Vermächtnisse aus: Einerseits ein politisches Erbe aus Zeiten des sozialistischen Regimes, anderseits - der friedlichen Revolution von 1989 folgend - ein Erbe politischen Umbruchs und Neuanfangs. Mittels Alter-Perioden-Kohortenmodelle basierend auf Daten des European Social Surveys (ESS) kann die Entwicklung des Protestverhaltens verschiedener Generationen und in verschiedenen Zeiträumen im Vergleich von Ost- und Westdeutschen untersucht werden. Die Ergebnisse zeigen, dass die Teilnahme an Demonstrationen, Petitionen und Boykotts für Ostdeutsche, die in der ehemaligen DDR sozialisiert wurden, niedriger ist als für Westdeutsche derselben Kohorte. Das Teilhabedefizit bleibt über die Zeit bestehen und steigt für einige Protestformen sogar leicht an.
Additional information: This is the preprint version of a paper published in Comparative Sociology. Reference: Joly, Philippe. “Generations and Protest in Eastern Germany: Between Revolution and Apathy.” Comparative Sociology 17, no. 6 (2018): 704–37. https://doi.org/10.1163/15691330-12341481.
Keywords: 320